Bureaucrats in the Formation of the State: Construction of Representations on Bureaucracy, 1839-1890 - Rodríguez Solano, Pablo Augusto (2019)
This article aims to analyze the ways in which the image of public officials of the nascent Costa Rican state is shaped through newspapers between 1839 and 1890– a critical period in the country´s institutional formation–. The concepts, symbols, signs, rituals and ceremonies, involved in the definition and maintenance of this image, evidences a translation process, which implies a continuous bureaucratization of the social space that led the spaces of the local and the central administration to get closer in the Costa Rican society, turning the bureaucracy into a bridge that united them, characterized by a confrontation between experience (as a practical way of custom in the local space) and knowledge (as an element of specialized technical training). The research questions the notion of modernity in the formation of the Costa Rican state and invites to rethink an agenda of analysis for the approach to the phenomenon of power during these key years.